BUILDING HARMONY THROUGH RELIGIOUS RECEPTION IN CULTURE: LESSON LEARNED FROM RADIN JAMBAT FOLKTALE OF LAMPUNG - Iswanto, Agus (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Understanding existed various religious receptions in culture provides a great opportunity for building and nurturing the harmony among religious followers and for enhancing solidarity within the society. This article uncovers receptions of religious aspects (ultimate truth/God, cosmological and religious ritual aspects) in the cultural products of Radin Jambat, a folktale from Lampung, Indonesia. This paper is based on the analysis of Radin Jambat folktale text, interviews, as well as additional library research of the Lampung cultural literary sources. Religious receptions as shown in Radin Jambat folktale indicate the preservation of past beliefs, coupled with the gentle addition and inclusion of Islamic teachings, to create harmony between religion and tradition through folktale. This study is evidence that Islam has been accepted by the societies of Lampung through gradual processes and varied receptions in terms of cultural values. This article shows that the important meaning of Radin Jambat folktale is a solid documentation to related sources about the concepts and practices of harmony among religious followers in Indonesia in the local tradition of Lampung with regards to cultural reception.